IMPLEMENTASI ARTIFICIAL INTELLIGENCE (AI) PADA SISTEM INFORMASI MANAJEMEN PENJUALAN - Rajagukguk, Yosia Suhendri; Darwis Robinson Manalu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of digital technology encourages companies to optimize their Sales Management Information Systems (MIS) through the application of Artificial Intelligence (AI). AI enables the automation of business processes, predictive data analysis, and personalization of customer services, which have an impact on increasing operational efficiency and company profitability. This study aims to analyze the forms of AI implementation in Sales MIS, the benefits generated, and the challenges faced in its application. The method used is a descriptive approach through literature studies, document analysis, and observation. The results of the study indicate that AI implementation increases operational efficiency, accelerates decision-making, and improves the quality of customer service. However, the main challenges include data quality, information privacy, and the readiness of human resources. This study recommends investment in data infrastructure, strengthening privacy policies, and employee training as effective implementation strategies.The development of digital technology encourages companies to optimize their Sales Management Information Systems (MIS) through the application of Artificial Intelligence (AI). AI enables the automation of business processes, predictive data analysis, and personalization of customer services, which have an impact on increasing operational efficiency and company profitability. This study aims to analyze the forms of AI implementation in Sales MIS, the benefits generated, and the challenges faced in its application. The method used is a descriptive approach through literature studies, document analysis, and observation. The results of the study indicate that AI implementation increases operational efficiency, accelerates decision-making, and improves the quality of customer service. However, the main challenges include data quality, information privacy, and the readiness of human resources. This study recommends investment in data infrastructure, strengthening privacy policies, and employee training as effective implementation strategies.